SOCIALIZATION OF CAKALANG CATCH RESULTS ON 20-60 GT BOATS AT MEUREDU FISH LANDING PARK (PPI), PIDIE JAYA DISTRICT - Wulan Agustria; Thaib Rizwan; Ilham Zulfahmi; Ichsan Setiawan; Sayyid Afdhal El Rahimi; Yulizar; Razali Thaib; Muhammad Arief; Syarifah Meurah Yuni; Husaini; Ratna Mutia Aprilla (Jurnal Pengabdian Bangsa, 2023)
This service aims to socialize the catch of skipjack tuna (Katsuwonus pelamis) at the Mereudu fish landing base (PPI), Pidie Jaya Regency using Purse seine fishing gear. Data collection carried out in this research used the field observation method by directly observing activities at the Mereudu Pidie Jaya Fish Landing Base (PPI) and conducting interviews with the parties involved in it. Fishing trips carried out by Pidie Jaya fishermen range from 5 days according to the catch that has been obtained. If the catch has reached the target, the fishermen immediately return even though it has not been 5 days. During the research, the highest number of catches of skipjack tuna was on 27 July 2022 with a catch of 5,000 kg and the lowest catch was on 29 July 2022 with a catch of 1,500 kg.